Studi Kebutuhan Hotmix di Provinsi Lampung - Tanjung, Frans Hasiholan; Sulistyorini, Rahayu; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This study was conducted to assess about the increase of hotmix requirement that is required for National and Provincial highway projects in Lampung Province in the year of 2014 and 2015 as well as the estimated requirement for the next three years. From the analysis and graphs show that the need for a hot mix road projects of national and provincial roads in the province of Lampung is still to be fulfilled by the availability of hot mix in AMP . For 2015 showed an increasing demand hotmix maximum time span exceeding 5 months AMP production capacity on average per month. The results of the analysis predicted increase hotmix in 2018 experienced a considerable difference between the need and availability of hot mix and amounted to 2 times as much and AMP provided feared not being able to meet the demand of maximum hotmix. Keywords: Hotmix, Asphalt Mixing Plant (AMP), National Road Projects, Provincial Road Projects